(untitled) (Journal of Information and Communication Technology, 2005)
With spending for computer and networking hardware, software and services projected to exceed a trillion pounds by 2005, the potential for greater involvement of ICT in the creation of organisation wealth could be hampered by an extremely high rate of project failures in ICT industry projects. The poor performance of the ICT industry in deploying its products has been demonstrated in numerous press reports. This paper reviews general knowledge on ICT project failure and proposes a hypothesis. The hypothesis states that â€œthe high rate of reported failures of ICT industry has been caused by the industry continuing to measure its success and failure rates based on in-appropriate criteria which fails to consider the industryâ€™s peculiar characteristics and the impact of ICT on organisational strategyâ€. A model that demonstrates this definition is developed from available literature.